Managing Assessment Practices in Islamic Education Through Formative and Summative Assessment - A'idatul Islahiah; Muhammad Raid Arrofi; Hafilda Anisa; Wardatul Hayati; Jaka Nugraha (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
This study aims to analyze how formative and summative assessments are managed in the context of Islamic education, particularly in Fiqh learning at Madrasah Aliyah Negeri (MAN). The research is motivated by the importance of assessment as a component of the Merdeka Curriculum and the need to understand its implementation and management strategies within religious education. The method used is quantitative with an ex post facto approach and multiple regression analysis technique. The sample consists of 100 eleventh-grade students at MAN 1 Bandung Regency. The results of the study indicate that both formative and summative assessments do not significantly influence students' learning outcomes in Fiqh, with a contribution of 0.1% (R² = 0.001). These findings highlight that while assessment practices are an important component, student learning success in Fiqh is more strongly influenced by institutional support and academic readiness. The study contributes to expanding understanding of how assessment practices can be effectively managed and integrated into values-based learning.